Pengaruh Penggunaan Media Pembelajaran Berbasis Teknologi terhadap Kemampuan Menulis Siswa Sekolah Dasar - Gani, Nursila; Meiarni, Ita (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
This study aims to explain the effect of using technology-based learning media on the writing skills of elementary school students. The low writing skills of some students are evident in their difficulty in developing ideas, using spelling, and constructing paragraphs logically. The development of digital technology provides opportunities for teachers to deliver more interactive, varied, and meaningful learning. This study uses a literature review method by examining various scientific sources related to literacy, learning media, and educational technology. The findings show that technology can increase motivation, participation, and writing quality, as well as facilitate the feedback process. These results confirm that the use of technology needs to be designed in a structured manner and in accordance with student characteristics